2019
DOI: 10.4265/bio.24.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Irradiation on <i>Penicillium</i> Strains Isolated from a Bread Plant and the Application to Bakery Products

Abstract: We tested treatement with UV irradiation for controlling the growth of bread mold. First, we analyzed the sterilizing effect of a dose of approximately 25 mJ/cm 2 radiation on nine Penicillium and two Talaromyces strains that were isolated from a bread-manufacturing plant. The P. chermesinum and P. paneum strains were sterilized completely at that dose, while it was only partially effective against P. corylophilum. P. chrysogenum and P. decumbens were sterilized at a dose of approximately 120 mJ/cm 2 , while T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…UV resistance in the genus Penicillium varies, depending on the species and strain ( 25 , 26 ). The members of Talaromyces are also resistant to UV radiation ( 27 , 28 ).…”
Section: Announcementmentioning
confidence: 99%
“…UV resistance in the genus Penicillium varies, depending on the species and strain ( 25 , 26 ). The members of Talaromyces are also resistant to UV radiation ( 27 , 28 ).…”
Section: Announcementmentioning
confidence: 99%
“…Anthocyanin concentrations were modified in cranberry water depending on the dose of UV-C light applied (0, 15, 30, 60, 120 and 240 mJ cm −2 ) with a tendency to decrease (10%) as the dose increased (240 mJ cm −2 ) recommending the UV-C light treatment dose of 40 mJ cm −2 [52]. On the other hand, it should be noted that studies related to the sensory preferences of consumers applying different doses UV-C (70, 140, and 210 mJ cm −2 ) on white bread, consumers preferred bread with the dose of 70 mJ cm −2 [70].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Although it has not only been proposed to sterilize bread in problems in the industry, but also to keep product lines in good sanitary condition. Kawaguchi (2019) [70] found that the most abundant and common fungus in bread is penicillium sp. In the application of this physical method, there is the problem that on the one hand the food product can be healthily benefited; but on the other hand, some nutritional components could be degraded.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Spores of A. niger showed the strongest resistance compared to the other moulds tested. Kawaguchi et al (2019) found that 70 mJ/cm² is effective in delaying mould growth of Penicillium spp. from 4 to 6 days without having to compromise on taste.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of surface cracks or small particles on bread (e.g. flour, grains) reduces the effectiveness of UV as some fungal spores might not be exposed to UV light directly (Begum et al, 2009;Kawaguchi et al, 2019). The fact that this technology does not emit heat nor causes condensation on the packaging is a positive aspect.…”
Section: Introductionmentioning
confidence: 99%